Corrosion resistance of Ni‐P\CePO4 coatings obtained from sol solutions. Issue 6 (28th August 2014) - Winiarski, J.; Gałuszka, M.; Stankiewicz, A.
<x xml:space="preserve">Abstract</x> Combined sol–gel and electroless plating techniques were used to obtain nickel‐matrix composite coatings. Scanning electron microscopy (SEM) was used to examine the surface morphology. Energy dispersive spectroscopy (EDS) was employed to analyze the composition of each coating. Corrosion resistance of the coatings was evaluated by electrochemical impedance spectroscopy (EIS). The composite Ni‐P\CePO4 coating was found to have better protective properties against corrosive environments than simple Ni‐P. EIS measurements showed that composite coatings had a higher corrosion resistance during first 4 days of exposure to non‐deaerated NaCl solution in comparison to Ni‐P. The longer the time of exposure (above 4 days), the protective properties of both types of coatings decreased. Eventually, after 16 days of immersion in a corrosive media, simple Ni‐P coating was partially damaged, while Ni‐P\CePO4 was still covering a substrate.